ASPEK HUKUM PIDANA PADA KEKERASAN DALAM RUMAH TANGGA - Fitra Oktoriny (Normative Jurnal Ilmiah Hukum, 2018)
Criminal acts are prohibited and threatened with crime, for short, they are called criminal acts, criminal acts or offenses. Regarding actions which are considered as criminal acts, the principle of legality is the principle which determines that no action can be punished except on the strength of the criminal rules in the existing laws and regulations, before the act is carried out (Article 1 paragraph (1) of the Criminal Code), it means that a person cannot be convicted of a criminal offense if there are no legal rules governing it first. That domestic violence has fulfilled the elements of criminal acts or criminal acts, menginggat forms of domestic violence also found in the Law in Criminal Law and the emergence of new offenses should be estimated more specific regulations.